The relationship between the ketuk tilu dance and the jaipongan dance - Agustina, Wina Resky (Mamaos:Journal Physical Education, Sport and Art, 2024)
The Ketuk Tilu Dance as a typical West Javanese folk dance which initially functioned as a ceremonial dance welcoming the rice harvest, and in its development has changed its function to become an entertainment and spectacle dance that usually appears on night market events, celebrations and so on. In the 1980s came the Jaipongan Dance created by Gugum Gumbira. So that makes dancers become more active. The appearance of the dance by Gugum Gumbira was originally called “Ketuk Tilu Development", which at first the work was still thick with the color of Ibing ketuk Tilu, both in terms of choreography and accompaniment. The dance is then more popularly known as Jaipongan. In its journey, Jaipongan is considered a emphasizes eroticism, because in the jaipongan dance it contains "3G" elements that are very vulgar namely geol, gitek, and rocking. But for Gugum Gumbira the viewpoint of eroticism is beauty, not what leads to sex appeal. Because if the so-called beauty or the usual carry to the erotic elements is not just rocking. The method used is observation, literacy, exploration, and improvisation. Meme in Jaipong Dance is tap tilu dance which is the forerunner to the creation of Jaipong Dance. In addition to the theory of picking this paper, there is also the theory of ideology, which was born from Gumbum Gumbira which creates patterns of motion in jaipong dance. then with its actualization proves that its emergence enriched the Sundanese dance in West Java with the pressure and encouragement so that the jaipong dance is now increasingly known to the international stage.